Evaluation of the vertical alterations of the upper second molars after the alignment and leveling phase using the MBT technique - Alael Barreiro Fernandes de Paiva Lino; Julio Wilson Vigorito (Dental Press Editora, 2013)
OBJECTIVE: This study aimed at comparing the distocervical angulations of upper second molars crowns of groups with normal occlusion and with Angle Class I and II malocclusions. Additionally, it aimed to analyze the changes occurring after alignment and leveling performed with MBT technique. METHODS: The sample of normal occlusions comprised 32 lateral teleradiographs, while the sample of malocclusions comprised 38 initial and post-leveling lateral teleradiographs. RESULTS: The results did not show statistically significant differences between morphological characteristics of the normal occlusion group and the malocclusion group. On the other hand, after alignment and leveling, statistically significant reduction was observed in distocervical inclinations with extrusion of the distal portion of upper second molars.